Comparison of influencing factors and level optimization for heating through deep-buried pipe based on Taguchi method. (March 2021) - Li, Chao; Guan, Yanling; Feng, Yinguo; Jiang, Chao; Zhen, Shengli; Su, Xunqing
Highlights: Evaluation parameters Q, COP, and R d of buried pipe heat transfer are discussed. Factors and corresponding levels affecting heat transfer in buried pipe are analyzed. Optimal level of factors at same weight of Q, COP, and R d is D4, G1, Tin 3, GG4, k4. Ranking of contribution rate at same weight of Q, COP, and R d is D, G, Tin, GG, k. Abstract: For building heating systems with a deep-buried coaxial double-pipe, its heat transfer performance was studied using three evaluation parameters in five heating periods under five factors and the corresponding four levels. The three evaluation parameters are time-averaged heat transfer per meter Q L-a, time-averaged performance parameter COP -a of heat pump unit, and five-year decay rate of heat exchange rate R d-5 . The five factors are buried pipe depth, water flow rate, inlet water temperature, geothermal gradient, and thermal conductivity of ground. The levels for each factor were selected in combination with practical problems. Sixteen sets of orthogonal simulation conditions (L16 4 5 ) with five factors and four levels were designed following the Taguchi method. Using signal-to-noise ratio and analysis of variance, Q L-a, COP -a, and R d-5 were evaluated under various factors and levels. The optimal combination of various factors for the best heat transfer performance of buried pipe and the contribution rate of each factor to the heat transfer performance of buried pipe were obtained.